Reliability evaluation of Sabah transmission and sub-transmission networks - Kamaruzaman, Ahmad Nassaruddin (2014)
Reliability planning criteria such N-1 and N-2 are measures of system wide reliability provided by an electricity distribution utility. These criteria also indirectly indicate the utility’s Operations and Maintenance (O&M) efficiency, system’s ability to transfer load to the neighbouring units in case of cable or equipment failures, response time to locate and isolate a fault and restoration time. This study considerably extends the modelling and evaluation techniques presently used in assessing the reliability of transmission networks. The concepts described lead to a realistic analysis of such systems. The most important features that are described concern the incorporation of value-based analysis, this often being of vital importance. In line with the new regulatory framework, Sabah Electricity Sdn Bhd took the opportunity to enhance its planning methods and approaches by adopting value-based approach to achieve optimum total cost of ownership. This paper presents an actual case study of detailed analysis on the connection schemes and substation configuration for a newly proposed 275/132kV substation. The outcome of the study results in a significant cost saving as compared to traditional approach. It was determined that the evaluation study based on the value-based analysis could save about twenty percent (20%) of project capital expenditure cost.